1990
DOI: 10.2169/internalmedicine1962.29.623
|View full text |Cite
|
Sign up to set email alerts
|

Silent thyroiditis with thyroid-stimulation-blocking antibodies(TSBAb).

Abstract: A 24-year-old man showed thyrotoxic symptoms with hypokalemic periodic paralysis. Serum thyroid hormone levels were high and thyrotropin (TSH) was undetectable. 123I-thyroidal uptake was suppressed. TSH-binding inhibitor immunoglobulin (TBII) was positive. After a month without any treatment, he became hypothyroid. Thyroid hormone level was decreased and TSHwas increased to above the normal range. 123I-thyroidal uptake was increased. TBII activity was still positive. From the clinical findings, a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
1
1
Order By: Relevance
“…Similarly, in the present case, TBAb and TSAb appeared at the same time, although three months later, TSAb levels had spontaneously decreased to just above the reference range in the hypothyroid phase, resulting in hypothyroidism from TBAb. Nakamura et al (10) also reported a 24-year-old man who was positive for TBAb but negative for TSAb during the hypothyroid phase of painless thyroiditis, which differs from our case.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Similarly, in the present case, TBAb and TSAb appeared at the same time, although three months later, TSAb levels had spontaneously decreased to just above the reference range in the hypothyroid phase, resulting in hypothyroidism from TBAb. Nakamura et al (10) also reported a 24-year-old man who was positive for TBAb but negative for TSAb during the hypothyroid phase of painless thyroiditis, which differs from our case.…”
Section: Discussioncontrasting
confidence: 84%
“…We herein report a rare case of painless thyroiditis that was positive for both TBAb and TSAb during the thyrotoxic phase. To date, only one case of painless thyroiditis in which TBAb was detected in the hypothyroid phase has been reported (10).…”
Section: Discussionmentioning
confidence: 99%
“…Our report supports this presentation. Silent thyroiditis has also been reported as an aetiological factor 57 . Other conditions, including TSH‐secreting pituitary adenoma, 58 ingestion of excessive thyroxine, 59 and iodine‐induced thyrotoxicosis with inadvertent use of iodine or with drugs containing iodine such as iodinate contrast agents or amiodarone, 60–62 have also been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…При этом у больных с АИТ часто встречается тандем, состоящий из ТСА и ТТГ БА, этиология которого пока неизвестна [40]. Ауто АТ к рецептору ТТГ способны имитиро вать функцию гормона и вызывать аутоиммунный процесс в результате связывания с рецептором ТТГ и последующей стимуляции (на имитационной осно ве) тиреоидных клеток ЩЖ [41]. ТСА, стимулирую щие функцию железы, усиливают продукцию тирео идных гормонов, тогда как ТТГ БА предотвращают активацию рецептора ТТГ и могут иметь значение в патогенезе атрофии железы и развитии гипотирео за у некоторых больных с АИТ [42].…”
Section: ауто ат к рецептору ттгunclassified